The ECG Atlas of Cardiac Rhythms - Doubell, Anton (SA Heart Journal, 2017)
In the introduction to his book, Rob Scott Millar states: “This is not a textbook. Its core value depends on the variety of real ECG traces and their interpretation which will, hopefully, assist you in interpreting similar rhythms that you encounter in your practises”. In stating thus, his humility may lead you to underestimate the value of this book which is filled with pearls that only an experienced electrophysiologist and enthusiastic teacher of Rob Scott Millar’s stature can provide. His humble description should rather read: “Its core value depends on the variety of real ECG traces and their interpretation which will definitely assist you in interpreting similar rhythms that you encounter in your practises.”